The Effect of Different Annealing Strategies on the Microstructure Development and Mechanical Response of Austempered Steels - Castro-Cerda, F; Hernandez-Duran, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This study focuses on the effect of non-conventional annealing strategies on the micro-structure and related mechanical properties of austempered steels. Multistep thermo-cycling (TC) and ultrafast heating (UFH) annealing were carried out and compared with the outcome obtained from a conventionally annealed (CA) 0.3C-2Mn-1.5Si steel. After the annealing path, steel samples were fast cooled and isothermally treated at 400 °C employing the same parameters. It was found that TC and UFH strategies produce an equivalent level of microstructural refinement. Neverthe-less, the obtained microstructure via TC has not led to an improvement in the mechanical properties in comparison with the CA steel. On the other hand, the steel grade produced via a combination of ultrafast heating annealing and austempering exhibits enhanced ductility without decreasing the strength level with respect to TC and CA, giving the best strength–ductility balance among the studied steels. The outstanding mechanical response exhibited by the UFH steel is related to the formation of heterogeneous distribution of ferrite, bainite and retained austenite in proportions 0.09–0.78–0.14. The microstructural formation after UFH is discussed in terms of chemical hetero-geneities in the parent austenite. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.